Mesenchymal Stem Cell Sheet Promotes Functional Recovery and Palliates Neuropathic Pain in a Subacute Spinal Cord Injury Model - Kazuyoshi Yamazaki; Masahito Kawabori; Toshitaka Seki; Soichiro Takamiya; Kotaro Konno; Masahiko Watanabe; Kiyohiro Houkin; Miki Fujimura (Stem Cells International)
Stem cell therapy has been shown to reverse the sequelae of spinal cord injury (SCI). Although the ideal treatment route remains unknown, providing a large number of stem cells to the injured site using less invasive techniques is critical to achieving maximal recovery. This study was conducted to determine whether administration of bone marrow stem cell (BMSC) sheet made on its own without a scaffold is superior to intramedullary cell transplantation in a rat subacute SCI model. Adult female Sprague-Dawley rats were subjected to SCI by 30 g clip compression at the level of Th6 and Th7 and were administered BMSC cell sheet (7×104 cells, subdural), cell suspension (7×104 cells, intramedullary), or control seven days after the injury. Motor and sensory assessments, as well as histological evaluation, were performed to determine the efficacy of the different cell transplantation procedures. While both the cell sheet and cell intramedullary injection groups showed significant motor recovery compared to the control group, the cell sheet group showed better results. Furthermore, the cell sheet group displayed a significant sensory recovery compared to the other groups. A histological evaluation revealed that the cell sheet group showed smaller injury lesion volume, less inflammation, and gliosis compared to other groups. Sensory-related fibers of μ-opioid receptors (MOR, interneuron) and hydroxytryptamine transporters (HTT, descending pain inhibitory pathway), located around the dorsal horn of the spinal cord at the caudal side of the SCI, were preserved only in the cell sheet group. Stem cells could also be found inside the peri-injured spinal cord in the cell sheet group. BMSC cell sheets were able to promote functional recovery and palliate neuropathic pain more effectively than intramedullary injections, thus serving as a good treatment option for SCI.